Economic Growth Through Tourism: A Global Analysis Using CS-ARDL Approach - Hussain, Altaf; Nawaz, Muhammad Atif (iRASD Journal of Economics, 2024)
This paper examines the effects of tourism receipts and governance on economic growth in a panel of 103 countries. The short-run results of the Cross-Sectional Autoregressive Distributed Lag (CS-ARDL) model, indicate that labour force and fixed capital positively impact on economic growth, highlighting the significance of investing in infrastructure and maintaining a vibrant workforce. The validity of the Tourism-Led Growth (TLG) theory in the short and as well as in the long-run has been proved by a robust and significant positive connection between tourism receipts and GDP growth. Surprisingly, the presence of mobile cellular subscriptions (ICT) in the model does not affect economic growth significantly, indicating the possibility of reaching a point of technical saturation. Trade has a substantial influence on short-term GDP growth, while the role of governance in economic development is complex and might depend on contextual settings. The results indicate that attraction of worldwide tourists can substantially impact economic growth. Further research should investigate the time-based and regional aspects of these connections to improve our comprehension of the dynamics of economic growth.